2017
DOI: 10.3390/md15070209
|View full text |Cite
|
Sign up to set email alerts
|

Bistratamides M and N, Oxazole-Thiazole Containing Cyclic Hexapeptides Isolated from Lissoclinum bistratum Interaction of Zinc (II) with Bistratamide K

Abstract: Two novel oxazole-thiazole containing cyclic hexapeptides, bistratamides M (1) and N (2) have been isolated from the marine ascidian Lissoclinum bistratum (L. bistratum) collected in Raja Ampat (Papua Bar, Indonesia). The planar structure of 1 and 2 was assigned on the basis of extensive 1D and 2D NMR spectroscopy and mass spectrometry. The absolute configuration of the amino acid residues in 1 and 2 was determined by the application of the Marfey’s and advanced Marfey’s methods after ozonolysis followed by ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Two additional bistratamides with antitumor activity, M (17) and N (18), were also characterized, as reported by Urda et al Overall, the 1 H NMR data of 17 and 18 presented a similar pattern to that of Dolastatin E (30) [40]. Of note, the structures of the peptides westiellamide [42], Dendroamides 19-21 [43], and Nostocyclamides 22 and 23 [12] are all related to Bistratamides 12-18.…”
Section: Bistratamides C D G H I M and Nsupporting
confidence: 55%
See 1 more Smart Citation
“…Two additional bistratamides with antitumor activity, M (17) and N (18), were also characterized, as reported by Urda et al Overall, the 1 H NMR data of 17 and 18 presented a similar pattern to that of Dolastatin E (30) [40]. Of note, the structures of the peptides westiellamide [42], Dendroamides 19-21 [43], and Nostocyclamides 22 and 23 [12] are all related to Bistratamides 12-18.…”
Section: Bistratamides C D G H I M and Nsupporting
confidence: 55%
“…Bistratamides C, D, G, H, I, M, and N (12)(13)(14)(15)(16)(17)(18) are cyclic hexapeptides that were isolated from the cytotoxic extract from the ascidian Lissoclinum bistratum (Figure 7) [39,40]. Sharing a similar cyclic backbone, the structures of 12-18 were determined by means of 2D NMR spectroscopy, as well as mass spectrometry.…”
Section: Bistratamides C D G H I M and Nmentioning
confidence: 99%
“…The metabolites reported in 2017 included carbamates 1428-1431, ureas 1432-1435 and isoquinoline 1436 (Didemnum molle), 656 isoquinoline-quinones 1437-1439 (Ascidia virginea), 657 antibacterial cadiolides J-M 1440, 1441-1443 (Pseudodistoma antinboja), 658 new congeners in the mandelalide series 1444-1450 (Lissoclinum mandelai), 659 cytotoxic bistratamides M and N 1451, 1452 (L. bistratum), 660 and cyclic hexapeptide dimers antatollamides A 1453 and B 1454 (D. molle). 661 The absolute conguration of the constituent amino acids of antatollamide A were secured by making use of a new tryptophan-based chiral derivatisation reagent.…”
Section: Molluscsmentioning
confidence: 99%
“…The copper concentration of ascidians is several orders of magnitude higher than seawater leading to the idea that some cyanobactins function in copper transport and storage, or detoxification [ 44 ]. Two novel cyclic hexapeptides—bistratamides M and N—differing only in the configuration of one alanine side chain ( Figure 1 ) have been isolated [ 45 ]. In the same study the authors also examined the metal binding of Bistratamide K and showed that it binds Zn(II).…”
Section: Cyanobactinsmentioning
confidence: 99%